2018
DOI: 10.1073/pnas.1801338115
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing isoxazoline veterinary drugs for control of vector-borne human diseases

Abstract: Isoxazolines are oral insecticidal drugs currently licensed for ectoparasite control in companion animals. Here we propose their use in humans for the reduction of vector-borne disease incidence. Fluralaner and afoxolaner rapidly killed ,, and mosquitoes and sand flies after feeding on a drug-supplemented blood meal, with IC values ranging from 33 to 575 nM, and were fully active against strains with preexisting resistance to common insecticides. Based on allometric scaling of preclinical pharmacokinetics data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 42 publications
(59 reference statements)
3
69
0
2
Order By: Relevance
“…The relationship between mosquito fecundity or mortality and the concentration of LLINs or systemic insecticides is not linear, but is captured by Hill kinetics. The F 50 , , and Hill coefficients ( H b and H d for birth and death rates, respectively) were calculated for lab-reared Anopheles for different systemic insecticides by fitting a Hill equation to published data (2729) ( Fig. S1-2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between mosquito fecundity or mortality and the concentration of LLINs or systemic insecticides is not linear, but is captured by Hill kinetics. The F 50 , , and Hill coefficients ( H b and H d for birth and death rates, respectively) were calculated for lab-reared Anopheles for different systemic insecticides by fitting a Hill equation to published data (2729) ( Fig. S1-2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The was calculated for wild Anopheles that displayed a range of resistance to LLINs and the Hill coefficient ( H n ) was calculated for lab-reared, permethrin resistant Anopheles by fitting a Hill equation to published data (30, 31). The time window ( T N or T D ) associated with each insecticide’s LC 50 was based on previously reported measurements (2729, 31).…”
Section: Methodsmentioning
confidence: 99%
“…Other possible factors behind the persistence of Rdl resistance alleles include the long half-life of dieldrin as an environmental organic pollutant; as well as the fact that Rdl is the target site of other insecticides such as fipronil, isoxazoline or meta-diamides (Gant et al 1998;Nakao and Banba 2015;Miglianico et al 2018); a secondary target of avermectin (Miglianico et al 2018), and, possibly, of neonicotinoids (imidacloprid), pyrethroids (deltamethrin) (Taylor-Wells et al…”
Section: Evolution Of Rdl Resistance: Selective Sweeps and Multiple Imentioning
confidence: 99%
“…This evolutionary trajectory has parallels with later-emerging target site resistance mutations, such as Vgsc (Martinez-Torres et al 1998; Davies et al 2007;Clarkson et al 2014;Clarkson et al 2018). The persistence of dieldrin resistance also challenges the efficacy of current and newly developed insecticides that also target Rdl (Gant et al 1998;Nakao and Banba 2015;Miglianico et al 2018), as well as the efficacy of rotative insecticide management strategies (World Health Organization 2012). These results thus emphasise the influence of past interventions on current and future programmes of vector population control.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in Burkina Faso observed a 20% reduction in clinical incidence in an intervention group receiving ivermectin 6 times over 18 weeks at 3 week intervals, with young children, pregnant women, and women nursing newborns excluded from MDA eligibility [16]. Another drug class, isoxazolines, shows promise to maintain mosquitocidal activity up to 50-90 days [17], although safety concerns still need to be addressed [18].…”
Section: Introductionmentioning
confidence: 99%